A software based design methodology for the design of low-cost electrical reticulation networks - Dwolatzky, B; Meyer, A.S (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
In South Africa, the challenge of the early 21st Century is to extend the supply of grid electricity to many of the currently unelectrified urban and rural households. As part of the recently elected government's reconstruction and development plan, the intention is to electrify 500,000 households per year for the next 10 to 15 years. This paper describes a research and development project being undertaken at the University of the Witwatersrand, in Johannesburg, aimed at providing the designers of electrical distribution networks with an integrated set of software tools. (3 pages)